Computation of new diagonal graph Ramsey numbers - Richard M. Low; Ardak Kapbasov; Arman Kapbasov; Sergey Bereg (Electronic Journal of Graph Theory and Applications (EJGTA), 2022)
For various connected simple graphs G, we extend the table of diagonal graph Ramsey numbers R(G, G) in ‘An Atlas of Graphs.’ This is accomplished by first converting the calculation of R(G, G) into a satisfiability problem in propositional logic. Mathematical arguments and scientific computing are then used to calculate R(G, G).